1973
DOI: 10.1128/jb.114.2.517-527.1973
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Aspartic Transcarbamylase in Sporulating Bacillus subtilis : Demonstration of a Requirement for Metabolic Energy

Abstract: The aspartic transcarbamylase (ATCase) activity of Bacillus subtilis cells disappears rapidly from stationary-phase cells prior to sporulation. ATCase activity does not appear in the culture fluid during the stationary phase; hence the enzyme appears to be inactivated in the cells. The enzyme is inactivated normally in two different mutants lacking proteases; the activity is very stable in crude extracts of cells or in the culture fluid. These results suggest that ATCase is not inactivated by the general prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…The second peak of protease activity (at 17 h; see Fig. 1) did not appear after fluoroacetate addition, which showed that the inhibitor did interfere with energy-yielding metabolism, as expected from earlier results (22,23). It is possible that the deprivation of energy induced by fluoroacetate was sufficient to block protease synthesis but not sufficiently extreme to block degradation.…”
Section: Inactivation Of Otcase In Vivo When B Sub-supporting
confidence: 76%
See 3 more Smart Citations
“…The second peak of protease activity (at 17 h; see Fig. 1) did not appear after fluoroacetate addition, which showed that the inhibitor did interfere with energy-yielding metabolism, as expected from earlier results (22,23). It is possible that the deprivation of energy induced by fluoroacetate was sufficient to block protease synthesis but not sufficiently extreme to block degradation.…”
Section: Inactivation Of Otcase In Vivo When B Sub-supporting
confidence: 76%
“…Unlike the inactivation of aspartate transcarbamylase in B. subtilis (22), the inactivation of OTCase was not inhibited by interfering with the generation of metabolic energy by addition of fluoroacetate. Inactivation was prevented by chloramphenicol, if the antibiotic was added before inactivation began.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The availability of the strains that produced pyrimidine enzymes constitutively enabled us to examine whether such synthesis was coordinate in cells that were grown under identical conditions in the presence of a constant excess of exogenous uracil and harvested during exponential growth. This was important because interference by inactivation of pyrimidine enzymes in the stationary phase or during pyrimidine starvation (7,11) could be avoided. Simultaneous synthesis and degradation of aspartate transcarbamylase during uracil starvation of B. subtilis cells has been demonstrated (5), and each of the other enzymes is inactivated in stationary cells (7; unpublished data).…”
mentioning
confidence: 99%